2007
DOI: 10.1177/1069072706294508
|View full text |Cite
|
Sign up to set email alerts
|

A Cluster-Analytic Investigation of Subtypes of Adult Career Counseling Clients: Toward a Taxonomy of Career Problems

Abstract: Two hundred and seventy-eight adults who ranged in age from 18 to 69 years and were voluntarily in career counseling completed measures pre- and postcounseling to assess career-related variables (e.g., vocational identity) and psychological issues that may affect career concerns (e.g., level of psychological distress). Participant-clients received 1 to 14 sessions of individual career counseling, according to the need of each participant. The counselors were trained to use a holistic method of career counselin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
29
0
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 41 publications
(52 reference statements)
2
29
0
5
Order By: Relevance
“…These findings are not surprising and are in line with previous studies (Albion & Fogarty, 2002; Bucki et al, 2015; Multon et al, 2007; Ryff, 2014). As expected, young adults’ higher levels of autonomy, personal growth, and self-acceptance appear to be related to higher confidence in their own ability to effectively engage in the activities of career planning and job searching.…”
Section: Discussionsupporting
confidence: 93%
“…These findings are not surprising and are in line with previous studies (Albion & Fogarty, 2002; Bucki et al, 2015; Multon et al, 2007; Ryff, 2014). As expected, young adults’ higher levels of autonomy, personal growth, and self-acceptance appear to be related to higher confidence in their own ability to effectively engage in the activities of career planning and job searching.…”
Section: Discussionsupporting
confidence: 93%
“…Kelly & Pulver, 2003;Multon et al, 2007;Rochlen et al, 2004), the ultimate goal should be to prescribe distinctive, effective interventions for different types of career indecision (Rojewski, 1994). For this reason, we agree with Kelly and Lee's (2002) recommendation urging '' .…”
Section: Discussionmentioning
confidence: 69%
“…It is not expected that career-decided individuals seek career counseling. However, a cluster analytical study by Multon et al (2007) with a sample of clients from a university counseling center showed that this assumption is not tenable. One of the subgroups identified, representing 16% of the sample, consisted of clients who were psychologically sound and had clear ideas about their career choices.…”
mentioning
confidence: 99%
“…This finding could be explained by the interconnectedness between the different domains of clients’ life (Gysbers, Heppner, & Johnston, 2014). Indeed, previous studies have found career and mental health concerns to be linked (e.g., Multon, Wood, Heppner, & Gysbers, 2007; Rottinghaus, Jenkins, & Jantzer, 2009; Saunders, Peterson, Sampson, & Reardon, 2000). Other studies have yielded statistically significant reductions of psychological distress during career counseling (Heppner et al, 2004; Multon, Heppner, Gysbers, Zook, & Ellis‐Kalton, 2001).…”
Section: Discussionmentioning
confidence: 99%